Shakespeare, Machiavelli, and Montaigne power and subjectivity from Richard II to Hamlet - Grady, Hugh (Oxford University Press, 2002)
Hugh Grady argues that in analysing modern subjectivity Shakespeare re-produced not the ideas of Machiavelli, but those of Michel de Montaigne, that Renaissance definer of shifting identities and subjectivities and of complexly formed, sceptical knowledge.